Arctic Flora and Fauna. Recommendations for Conservation. 2002. - Conservation of Arctic Flora and Fauna (CAFF) (Conservation of Arctic Flora and Fauna (CAFF), 2002)
The Arctic Council working group Conservation of Arctic Flora and Fauna (CAFF)'s booklet 'Recommendations for Conservations', presented at the Arctic Council's Ministerial Meeting in Inari, Finland, October 9-10 2002.